2021
DOI: 10.1002/adom.202002197
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances of Cocrystals with Room Temperature Phosphorescence

Abstract: bioavailability, etc.) can be modified by cocrystallization with coformers. Beyond active pharmaceutical ingredients, cocrystallization is being extensively or has also been established as a effective technique to change or improve the photoluminescence (PL) properties of the organic materials, [2][3][4][5][6] along with to discover the structure-property associations at a molecular level. [7,8] Room temperature phosphorescence (RTP), continuously one of the dynamic research fields in science and technology cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
129
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(134 citation statements)
references
References 91 publications
0
129
0
Order By: Relevance
“…Intense study has shown that heteroatoms (N, O, and S) or corresponding functional groups are especially useful in realizing efficient RTP. [ 106 ] Therefore, carbazole, [ 107 ] indoline, [ 108 ] quinoline, [ 109 ] phenothiazine, [ 110 ] and their derivatives [ 111 ] account for the majority of RTP luminophores. The reason is simple: these atoms and related moieties bear lone pairs which enhance the rate of the ISC process through El‐Sayed's rule.…”
Section: Discussionmentioning
confidence: 99%
“…Intense study has shown that heteroatoms (N, O, and S) or corresponding functional groups are especially useful in realizing efficient RTP. [ 106 ] Therefore, carbazole, [ 107 ] indoline, [ 108 ] quinoline, [ 109 ] phenothiazine, [ 110 ] and their derivatives [ 111 ] account for the majority of RTP luminophores. The reason is simple: these atoms and related moieties bear lone pairs which enhance the rate of the ISC process through El‐Sayed's rule.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] Among them, halogen substitution has been proved to be one of the most effective design strategies. 15,16 The introduction of different halogen elements will realize OPL emission with signicantly tuneable intensity and lifetimes, making halide-containing OPL materials applicable to different environment sensing scenarios. 10,17 In addition, halogen elements contribute to the formation of halogen bond networks, remarkably restricting molecular motion or vibration and boosting the OPL emission.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with fluorescence, phosphorescence involves longer excited lifetimes, larger Stokes shifts, and higher signal‐to‐noise ratios. [ 1–3 ] Because of these advantages, phosphorescent materials have great potential for use in sensors, [ 4,5 ] biological imaging, [ 6,7 ] light‐emitting diodes (LEDs), [ 8,9 ] information encryption, [ 10,11 ] and anticounterfeiting. [ 12,13 ]…”
Section: Introductionmentioning
confidence: 99%